Letter : Spanish seamen - Deakin, Arthur
025a-0023-001 Telegraphic Address TRADESUNION SOWEST LONDON Telephone Victoria 7671/5 Transport and General Workers' Union Registered Trade Union No. 18341. Approved Society for National Health Insurance No. 398 Registered Offices Transport House, Smith Square Westminster, London, S.W.1. General Secretary Ernest Bevin Financial Secretary Stanley Hirst Asst General Secretary Arthur Deakin Your Ref: HVT/FC/KA/37 Our Ref: 18th November, 1940. Sir Walter Citrine, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Sir Walter, SPANISH SEAMEN. I have to refer to Mr. Tewson's letter of the 29th ultimo which was brought before my Executive Council at their meeting held last week. As a result I am to state that the Council agreed that the Union's quota of the additional grant of £1,000 should be met, and accordingly you will be receiving from our Financial Secretary in due course a cheque for the amount involved, namely £280. In conveying this decision to you, I am to express the hope on behalf of my Executive Council that there will be no occasion for any further financial calls in respect of this particular case. Yours sincerely, Arthur Deakin ACTING GENERAL SECRETARY 292/946/25a/23